Pengaruh Kepentingan Nasional dan Interdependensi Ekonomi Terhadap Kebijakan Expeditious Disengagement Tiongkok-India pada Krisis Doklam 2017 - Wahyu Sri Rejeki; Tri Cahyo Utomo (Journal of International Relations Diponegoro, 2019)
The Doklam crisis occurred in 2017 and caused increased tensions between China and India, which had relatively more stable relations after the 1962 war. The crisis was caused by direct violations committed by China by building roads in the border region with Bhutan. The border of Doklam which triggers tension is a border area between China and Bhutan, while Bhutan is a country that legally receives military protection from India according to the 1949 Friendship treaty agreement. Tensions between the two countries decreased with an agreement for 'expeditious disengagement' to restore the 'status quo', the agreement took place quickly even though the two countries were previously at odds with each other. This study aims to analyze the factors that led to the achievement of policies to reduce tensions between China and India. This study uses a qualitative method using the concepts of national interest and economic interdependence. The results of this study indicate that expeditious disengagement policy to reduce tensions between China and India is influenced by the concept of national interests and economic interdependence.